Culture-independent characterization of the bacterioplankton community composition of a mesotrophic reservoir (Embalse Río III, Argentina) Caracterización independiente de la composición de la comunidad del bacterioplancton en un embalse mesotrófico (embalse Río III, Argentina) - Daniela Polverino; Alejandro J. Mariñelarena; Christina B. McCarthy; Rolando V Rivera-Pomar (Revista Mexicana de Biodiversidad, 2012)
This study represents the first analysis of the bacterioplankton community structure from a freshwater reservoir of Argentina using amplification of the entire 16S rDNA gene. It includes the description and the phylogenetic relationships of the bacterioplankton community from the photic and aphotic layers of the Río III Reservoir in Córdoba, Argentina. The classical ecological approach indicated that the photic layer had greater diversity whereas the aphotic layer had a better distribution of species and higher abundance. Nevertheless, when the microbial communities in both layers were compared using phylogenetic information, this analysis indicated that both environments were similar and that neither was enriched for any particular lineage. The phyla present in the Río III reservoir were Acidobacteria, Actinobacteria, and Proteobacteria and the 2 dominant species in both layers were "Candidatus Planktophila sp." (class Actinobacteria) and Polynucleobacter sp. (class Betaproteobacteria). Este estudio constituye el primer análisis de la estructura de la comunidad del bacterioplancton en un reservorio de agua dulce de Argentina utilizando amplificación completa del gen ADNr 16S. Incluye las relaciones filogenéticas y una descripción del bacterioplacton de las zonas fótica y afótica del Embalse Río III, Córdoba, Argentina. El análisis ecológico clásico indicó que la zona fótica tenía mayor diversidad, mientras que la afótica tenía mayor abundancia y una distribución más uniforme de especies. Sin embargo, cuando se utilizó la información filogenética para comparar las comunidades microbianas de ambas zonas, este análisis indicó que ambos ambientes eran similares y que en ninguno predominaba algún linaje en particular. Los phyla identificados en el Embalse del Río III fueron Acidobacteria, Actinobacteria y Proteobacteria. Las especies dominantes en ambas zonas fueron "Candidatus Planktophila sp." (clase Actinobacteria) y Polynucleobacter sp. (clase Betaproteobacteria).